Water Ritual at Balamut Oral Tradition of Banjar People, South Borneo, Indonesia - Sainul Hermawan (Asean Study Center Lambung Mangkurat University, 2021)
Some Southeast Asian Nations have water rituals. This article explores one of water rituals in Indonesia, namely Balamut. Balamut is one of oral traditions in Banjarmasin performed both for entertaining and healing. This paper aims to relate this tradition to its place, Banjarmasin that often called as a city of thousands river. There is no direct connection between the traditions of balamut and rivers, but there is no balamut hajat (balamut for thanksgiving) and or tatamba (healing) if there is no water. Nevertheless, my observations of some of the rituals of balamut hajat and healing performed by Pak Jamhar Akbar, one of the palamutan in Banjarmasin, indicate that the Banjarese people who conduct this ritual generally lived near the river (Jingah River, Tabuk River, Kalayan River, Kuin River). In the past, the river was certainly the main source of water used in this ritual. Although some Banjarmasin people now get clean water through PDAM (regional water factory), this ritual symbolically shows Banjar beliefs in the magical power of water. When the community heard that there would be a balamut ritual, they came with a bottle in various sizes. The water they carry is not only sourced from the taps, but also the bottled water from a very remote place. The water spread out in the sacred arena is believed to be able to provide various benefits for those who believe in it: curing disease, increasing luck, and so forth. Water rites in general mean a variety of human activities that are routine or repeated use as a medium that is very important and fundamental.